Experimental Analysis for Low Power Series-Series Compensated Inductive Power Transfer System - de Lacerda, Macklyster Lanucy Scherre Stofel; Macedo, Tatiana Saviato; Martins, Denizar Cruz; Marques dos Santos, Walbermark (Brazilian Power Electronics Conference (Congresso Brasileiro de Eletrônica de Potência), 2019)
The research in wireless power transfer has grown in the last years, motivated mainly by the convenience and the security that technology offers, including applications where the feeding of equipment by cables is technically complicated or dangerous. Among the wireless transfer technologies, the Inductive Power Transfer (IPT) has been highlighted in several works in the literature. However, because it is an emerging technology, the subject still has an opportunity for analysis. In this paper, experimental results of a 20 W IPT system were used to validate a simplified Thevenin equivalent circuit (which directly relates the input and output DC voltages) and a coupling factor k equation as a function of the circuit measurable electrical parameters. Power has been limited due to available Litz wire specifications. The equations are supported with computational simulations and experimental results.